Carbon–Oxygen‐Bridged Ladder‐Type Building Blocks for Highly Efficient Nonfullerene Acceptors. Issue 45 (31st October 2018) - Xiao, Zuo; Yang, Shangfeng; Yang, Zhou; Yang, Junliang; Yip, Hin‐Lap; Zhang, Fujun; He, Feng; Wang, Tao; Wang, Jizheng; Yuan, Yongbo; Yang, Huai; Wang, Mingkui; et al.
Abstract: Recently, acceptor–donor–acceptor (A–D–A) small molecules have emerged as promising nonfullerene acceptors (NFAs) for organic solar cells and have attracted great attention. The carbon‐bridged (C‐bridged) ladder‐type D unit plays a crucial role in developing high‐performance A–D–A NFAs. However, the medium electron‐donating capability of C‐bridged units is unfavorable for making NFAs with strong light‐harvesting capability. In this regard, carbon–oxygen‐bridged (CO‐bridged) ladder‐type units present advantages in developing strong light‐absorbing NFAs. Here, recent progress in the newly emerging CO‐bridged NFAs is highlighted. The synthetic methods for the polycyclic CO‐bridged building blocks are introduced. The photovoltaic performance for CO‐bridged NFAs is summarized and discussed. Perspectives on developing high‐performance CO‐bridged‐NFA‐based solar cells are made. Abstract : Thanks to the strong electron‐donating capability of carbon–oxygen‐bridged (CO‐bridged) ladder‐type building blocks, CO‐bridged nonfullerene acceptors (NFAs) present low bandgaps and strong light‐harvesting capability, delivering high short‐circuit current density (>28 mA cm −2 ) and high power conversion efficiency (>14% for single‐junction and >17% for tandem) in organic solar cells.